Construction of Meaning in Verbal Communication - Liliweri, Alo; Widowati, Dewi; Manafe, Yermia Djefri (Advances in Social Sciences Research Journal, 2023)
In the social sciences, coordinated meaning management (CMM) provides an understanding of how individuals create, coordinate, and manage meaning in their communication processes. In general, it refers to "how individuals establish rules for creating and interpreting meaning and how those rules are related in conversation where meanings are constantly coordinated". (West and Lynn, 2007)." Human communication is seen as a flexible, open and changeable process that develops in continuous mutual interaction, which allows movements, shifts, and ways of evolving with one another". According to Miller and Sarah (2019). CMM embodies this vision and enables interpersonal connections and open conversations between individuals or groups, and can be applied across a wide range of academic fields and social scenarios.